Estimated Impact of Screening on Gonorrhea Epidemiology in the United States: Insights From a Mathematical Model. Issue 11 (November 2018) - Tuite, Ashleigh R; Rönn, Minttu M; Wolf, Emory E; Gift, Thomas L; Chesson, Harrell W; Berruti, Andres; Galer, Kara; Menzies, Nicolas A; Hsu, Katherine; Salomon, Joshua A
Background: The burden of gonorrhea infections in the United States is high. There are marked disparities by race/ethnicity and sexual orientation. We quantified the impact of screening and treatment on gonorrhea rates in the US population aged 15 to 39 years for the period 2000 to 2015 and estimated the impact that alternative screening strategies might have had over the same period. Methods: We developed a national-level transmission model that divides the population by race/ethnicity, preferred gender of sex partners, age, gender, and sexual activity level. We compared our fitted model ("base case") to 4 alternative strategies: (i) no screening, (ii) full adherence to current screening guidelines, (iii) annual universal screening, or (iv) enhanced screening in groups with the highest infection burden. Main outcomes were incidence, infections averted, and incidence rate ratios by race/ethnicity. Mean values and 95% credible intervals were calculated from 1000 draws from parameter posterior distributions. Results: The calibrated model reproduced observed trends in gonorrhea, including disparities in infection burden by race/ethnicity. We estimated that screening for gonorrhea from 2000 to 2015 averted 30% (95% credible intervals, 18–44%) of total infections that would otherwise have occurred. All alternative active screening strategies were estimated to further reduce, but not eliminate, gonorrhea infections relative to the base case, with differential impacts on the subpopulations of interest. Conclusions: Our model results suggest that screening has reduced gonorrhea incidence in the US population. Additional reductions in infection burden may have been possible over this period with increased screening, but elimination was unlikely. Abstract : A mathematical model of gonorrhea suggests that screening has reduced infection burden in the United States population but has likely had differential impact on different population groups. Supplemental digital content is available in the text.